PERANCANGAN PENGELOLAAN DONASI KEGIATAN SOSIAL BERBASIS APLIKASI CROWDFUNDING - Widiantoro, Suryo; Nestroldy, Milson (Program Studi Sistem Informasi Institut Indobaru Nasional, 2025)
During a sluggish economy, certain groups of society are impacted. Not only the people which economically disadvantaged, but also the middle-income group feels the impact of the unfavorable economic climate. One solution to help alleviate this burden is to raise funds for donations to those in need. Within higher education institutions environment scope, one example of a routine activity is social service of distributing basic necessities to economically disadvantaged communities around campus. The challenges faced relate to managing activities and receiving donations from donors. This web-based crowdfunding application is intended to help facilitate fundraising activities for the committee, thereby improving accountability and transparency, as all donor income is recorded in the system. The design method used is waterfall model with object-oriented approach to represent design diagrams required. The application was developed using PHP and MySQL database within an Apache server environment. Testing results to a limited user demonstrates that the system can operate smoothly, and further can be used by higher education institutions to manage fundraising activities for other needs.